"Povo": percursos de um conceito em Portugal 1780-1850 - Fátima Sá e Melo Ferreira (Araucaria)
In this article are highlighted some of the main paths covered by the term people, in Portugal in the last decades of the XVIIIth century and in the first half of the XIXth century. The most significant semantic variations that the word suffered in the backdrop of the political conflicts caused by the establishment of Liberalism are investigated, taking in consideration that the modern political uses of this word arose with the French Invasions (1807-1811) and with the resistance to those invasions by a part of the Portuguese population.